2019
DOI: 10.1002/2475-8876.12131
|View full text |Cite
|
Sign up to set email alerts
|

Global Hospitals in 2050—A review of the historical development of hospital building studies from a global perspective

Abstract: This paper aims to discuss the problems in the field of architectural planning and design and possible solutions to these problems by studying hospital buildings that have been developing in the latter half of the 20th century to meet the changing needs of healthcare provision for the super aging society in these days. The methodology used in this study involves reviewing the historical development of hospital building studies from a global perspective. This is followed by an explanation of the need underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Even in this day and age of technology, proper healthcare facilities and the availability of hospital buildings are the challenges [1] to be overcome. Recently, a universal hospital building model is suggested to address this important need [2]. Due to the economic and technological requirements, public space is only to satisfy the people flow, whereas no consideration has been paid to take into account the psychological needs of users.…”
Section: Introductionmentioning
confidence: 99%
“…Even in this day and age of technology, proper healthcare facilities and the availability of hospital buildings are the challenges [1] to be overcome. Recently, a universal hospital building model is suggested to address this important need [2]. Due to the economic and technological requirements, public space is only to satisfy the people flow, whereas no consideration has been paid to take into account the psychological needs of users.…”
Section: Introductionmentioning
confidence: 99%
“…High-tech medicine will develop faster and more sophisticated the way in the 21 st century and will be applied on a critical basis life-saving care and hospitals, as in the provision of emergency care, cancer, and heart attacks treatment (Nagasawa, 2020). Moreover, Adaptive reuse is converting the original function of existing buildings whose services and technology are outdated to a new building purpose for new need to meet the current development (Hasan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Flexibility is often a requirement that must be built into the organization's plans to anticipate growth and facility changes. In other words, the hospital complex consists of not only one building but a network of buildings with various structures and materials, each of which has different standards and technical conditions (Nagasawa, 2020). The novelty of this study indicated that to make adjustments to new functions that respect the authenticity of the heritage buildings, it should be considering adjustments of the space requirements in the future, rearranging the spatial layout with the concept of retrofitting, paying attention to the characteristics of existing buildings, and choosing a structural system that is relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hospital is not simply a building but as well a complex community institution. In considering the upcoming outlook of function-oriented hospitals and other healthcare services, the lately made concept, that is "healing environment", provides specific basis approaches to understanding various issues [9]. The constructing process of healthcare facilities, in any case, involves complex trade-offs with iterative activities such that design properties that have showing to improve building accomplishment are frequently not wholly considered.…”
Section: Literature Reviewmentioning
confidence: 99%